Complaint Discourse Features in Modality Forms: A Comparative Analysis of Japanese and Indonesian Internet Review - Rustandi, Andhini Pratami Putri (Universitas Pendidikan Indonesia (Indonesia University of Education), 2022)
This paper describes a comparative study of complaint discourse in Japanese and Indonesian focusing on modality expression. 500 items of each language were collected from TripAdvisor and usage of modality were quantitatively and qualitatively analyzed. As a result, modality forms have often been reported to be used to show consideration for the other person, such as avoidance of judgments and euphemisms, roundabout expressions or consideration (hairyo) for the other person are expressed. It was confirmed in complaint discourse, that there are cases in which have no consideration (hairyo) for the other person at all, rather than in a direct way of speaking. Both Japanese and Indonesian modality functioned effectively for expressing complaint. It was found that in “obvious complaint” the modality emphasizes the hotel’s faults and forces them to work appropriately, and in “implicit complaint”, the modality can express complaint with slightly reducing the burden on the hotel side by emphasizing the self-pay. The subject is used to determine whether an utterance expressing Complaint is “explicit/direct” or “implicit/indirect” in terms of the discourse level. In other words, the degree of FTA (Face Threat Act) differs depending on whether the subject is the writer (the guest) or the reader (the hotel). When the subject of “an act” is the reader (hotel side), the modality form functions to emphasize the reader’s fault (wrongness) or to force the reader (hotel side) to act. On the other hand, when the subject of “an act” was the writer, the function was to emphasize self- imposed burden or to understate the fault/burden of the reader (the hotel side).